Compact heat pipe heat exchanger for waste heat recovery within a low-temperature range - Seo, Jin Hyeuk; Kang, Sukkyung; Kim, Kyuil; Lee, Jungho (International Communications in Heat and Mass Transfer, 2024)
Heat pipe heat exchangers (HPHX) are attracting attention for being capable of effective heat exchange through phase change. Much waste heat is generated at low-temperature sources, but there has been a lack of research on this. Most previous studies focus on large HPHXs over 1 m in length. In the present study, a compact HPHX (185 × 70 × 140 mm3) with nine heat pipes was fabricated, and the potential for waste heat recovery (WHR) was investigated at low heat sources. Also, the thermal performance of the HPHX was compared with and without the fin of the heat pipe. Experiments were conducted by changing the hot-side gas temperatures (50, 75, 100, and 125 °C) and mass flow rates (0.03, 0.04, and 0.05 kg/s). The heat transfer rate and pressure loss had a linear relationship with the hot-side temperature and mass flow rate. Despite a low temperature 50 °C, more than 100 W of heat can be recovered using a compact HPHX. At least 1.8 times improved thermal performance was obtained in HPHX in which finned heat pipes were installed. These results are expected to serve as indicators for various applications that generate low-temperature waste heat, such as clothes dryers and kitchen hoods.
Keywords: Compact heat pipe heat exchanger; Heat pipe heat exchanger; Heat pipe heat exchangers; Low-temperature source; Lows-temperatures; Mass-flow rate; Temperature range; Thermal Performance; Waste-heat recovery; Compact HPHX; Heat pipe heat exchanger (HPHX); Low-temperature source; Thermal performance; Thermal resistance